Construction somatic and motor skills 8-aged players with LKS Szubinianka Szubin - Bethke, Klaudia; Napierała, Marek; Gotowski, Rafał (Journal of Education, Health and Sport, 2017)
The aim of this study was to determine the status of the construction of somatic and motor skills-training eight years of boys playing football in Szubinianka LKS Szubin. The study was conducted in a group of eight-year seventeen boys. In order to assess the level of motor skills tests were used to selected the International Physical Fitness Test. In order to evaluate the construction of a somatic was measured height and weight, and these results were used to determine BMI and body type according to the characteristics Kretschmer using Rohrer index. Conclusions: (1) Respondents characterized by a slightly larger values of height and weight, but the differences are not statistically significant, (2) Most players characterized leptosomatyczna silhouette and normal weight, (3) Subjects exhibit a slightly higher level of efficiency than their peers, but these differences are not statistically significant, (4) Agility and speed of respondents are at a much better level than their peers.